2021
DOI: 10.21315/tlsr2021.32.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant-rich Clove Extract, A Strong Antimicrobial Agent against Urinary Tract Infections-causing Bacteria in vitro

Abstract: Clove (Syzygium aromaticum) is an exotic culinary spice that has been used for centuries due to its known antimicrobial and antioxidant properties. The main aim of this study is to compare the antimicrobial activity and antioxidant capacity of clove ethanolic extract (CEE) and commercial clove essential oil (CEO) at a standardised eugenol content. Disk diffusion assay showed that CEE (2000 μg) was able to exhibit broad-spectrum inhibition against both Gram negative and Gram positive Urinary Tract Infections (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…As for characterization methods, the most used among the literature were HPLC and the Folin–Ciocalteu method [ 23 , 26 , 30 , 33 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The combination of the former coupled with the mass spectrometry has also been widely used as an analytical characterization method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for characterization methods, the most used among the literature were HPLC and the Folin–Ciocalteu method [ 23 , 26 , 30 , 33 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The combination of the former coupled with the mass spectrometry has also been widely used as an analytical characterization method.…”
Section: Resultsmentioning
confidence: 99%
“…Among the extracts considered, clove ethanolic extract, along with Punica granatum, showed the best antimicrobial activity in fish-derived products. Additionally, their antimicrobial properties are further demonstrated in Rosarior et al (2021), where clove extracts showed an in vitro antimicrobial effect against urinary tract infections (UTI) caused by Proteus mirabilis and Staphylococcus epidermidis [40]. This bioactivity has been exceptional for their aqueous extracts.…”
Section: Solid-liquid Extraction and Sfementioning
confidence: 99%
“…Singh [ 44 ] reported that clove extract exhibited higher antimicrobial activity (17–25 mm inhibition zone) against E. coli , L. monocytogenes , Pseudomonas aeruginosa , S. aureus , and S. epidermidis compared with the antibiotic Cefotaxime (8–10 mm inhibition zone). Rosarior [ 45 ] stated that 2000 μg of clove ethanolic extract showed broad-spectrum inhibition (12.3–19.7 mm inhibition zone) against E. coli , K. pneumonia , Proteus mirabilis , S. aureus , and S. epidermidis . The antimicrobial activity of clove extract in the present study could be attributed to phenolic compounds such as quercetin, (+)-catechin, gallic acid, catechol, and protocatechuic acid [ 46 ], which are present in high quantities in the extract.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies on essential oils reported antibacterial effects against Gram-negative bacterial strains causing urinary tract infections [ 41 ]. The anti-MRSA potential of clove oil has also been reported and has highlighted the need to explore bioactive constituents [ 42 ].…”
Section: Discussionmentioning
confidence: 99%